Bio-economic evaluation of cropping systems for saline coastal Bangladesh: II. Economic viability in historical and future environments. (July 2017) - Kabir, Jahangir; Cramb, Rob; Gaydon, Donald S.; Roth, Christian H.
Abstract: The objective of this study was to assess the impacts of climate change and salinity on the economic viability of rice-based cropping systems under farmers' current management across current and future climate and salinity scenarios in south-west coastal Bangladesh. Detailed case studies were conducted in two contrasting coastal villages in Dacope Sub-district, Khulna District. Enterprise budgets were developed using APSIM-simulated and extrapolated yields together with crop management, cost, and price data obtained from the villages and estimated from various sources. The projected impact of climate change and salinization on the economic viability (profitability and riskiness) of most cropping systems was not pronounced. Thus rice-based cropping systems are likely to remain viable in both optimistic and pessimistic climate scenarios in coming decades, even allowing for salinization, because some of the positive effects of climate change were projected to offset the sizeable losses due to salinity. Moreover, where small yield declines were projected these were often offset by higher future prices. Sustainably-managed rice/shrimp cropping systems are likely to remain the most profitable option in locations with access to tidal saline water. In other sites, given adequate freshwater for irrigation in the dry season, rice/non-rice cropping systems were projected to be the most viable options, especially incorporating newer crops such as sunflower and maize. Dry-season rice and wheat were not projected to be viable options. Highlights: Rice-based cropping systems are likely to remain viable in coming decades, even allowing for salinization. Rice/shrimp systems are likely to remain the most profitable option where farmers have access to tidal saline water. Given adequate irrigation, rice/sunflower and rice/maize systems are likely to become preferred options. Dry-season rice and wheat are not projected to be viable options. There would be even more profitable cropping options if salinity in the region could be mitigated.